Degradasi Zat Warna Methyl Orange dengan Katalis ZnO-Co Menggunakan Metode Fotosonolisis - Laila Suryani; Hary Sanjaya; Yohandri Yohandri (Departemen Kimia FMIPA UNP, 2021)
Degradation of methyl orange was carried out with variations in time of 30, 60, 90, 120, 150, 180, 210, 240 minutes and variations in doped catalyst concentrations of 5%, 10%, 15%, 20%, 25% using the photosonolysis method. The results showed that the maximum degradation time of methyl orange was 210 minutes with a degradation percentage of 76.1216%. The variation in the concentration of catalyst for the degradation of methyl orange obtained a maximum concentration of 5% with a degradation percentage of 20.1045%. The band gap value of 5% ZnO-Co catalyst performed using UV-Vis Diffuse Reflectance Spectroscopy (DRS) was 3.21 eV.